Fatty acid-requiring mutant of Saccharomyces cerevisiae defective in acetyl-CoA carboxylase. - Roggenkamp, R (1980)
The isolation and biochemical properties of a Saccharomyces cerevisiae mutant (acc1-167) defective in acetyl-CoA carboxylase [acetyl-CoA:carbon-dioxide ligase (ADP forming), EC 6.4.1.2] activity are described. The mutant is deficient in de novo biosynthesis of long-chain fatty acids and specifically requires a saturated fatty acid of chain length 14-16 C atoms for growth. Fatty acid synthetase levels were normal, but the acetyl-CoA carboxylase specific activity of the purified enzyme was reduced to approximately 5% compared to wild-type yeast. Upon sodium dodecyl sulfate/polyacrylamide gel electrophoresis the purified mutant enzyme migrated as a single band and was essentially indistinguishable from the wild-type enzyme. The study of acetyl-CoA carboxylase partial activities revealed that the biotin incorporation capacity and the transcarboxylase partial activity were unaffected whereas the biotin carboxylase component enzyme exhibited less than 10% of wild-type specific activity. This biotin carboxylase mutational deficiency could be ascribed to a more than 90% reduction of Vmax and to a comparable increase in the Km value for ATP, which was accompanied by an increased requirement for Mg2+. It is concluded that acc1-167 contains a structural gene mutation in the biotin carboxylase domain of acetyl-CoA carboxylase.